Dor e disfunção craniocervicomandibular, ansiedade e depressão em profissionais da enfermagem sob estresse no trabalho - Pozzebon, Daniela (2015)
Studies indicate that the temporomandibular disorders (TMD) affects 7-15% of the adult population. In cases of recurrent pain, there is a decreased quality of life due to psychological impairment, physical disability and functional limitation. Stress at work has been shown to be an important causative agent of diseases. This study aimed to verify and correlate the presence of pain and craniocervicomandibular dysfunction, anxiety and depression in nursing professionals under stress at work. The study included 43 women at moderate and high levels of exposure to stress at work, diagnosed by at Job Stress Scale (JSS). The pain pressure threshold of the masticatory and cervical muscles, through algometry; TMD diagnosis and level of pain on palpation were verified using the instrument Diagnostic Criteria for Research on Temporomandibular Disorders (RDC / TMD) and its severity, by the Temporomandibular Index (TI). Additionally, it was verified the presence of anxiety and depression, by the Hospital Anxiety and Depression Scale (HADS); the perception of stress, by the Perceived Stress Scale (PSS) and the presence of headache and neck pain, as reported by the participants. Thirteen women (30.23%) were diagnosed with TMD, with mean value of TI of 0.52. Headache and neck pain were reported by 55.81% and 60.47% of the sample, respectively. Moderate low level of perceived stress was detected in 62.79%, anxiety in 16.63% and depression in 9.3% of the sample. Correlations were observed between pain intensity levels on manual palpation with perceived stress (r = 0.430, p = 0.004) and betwen psychosocial scales: perceived stress and anxiety (r = 0.579, p = 0.000), perceived stress and depression (r = 0,601, p = 0,000), anxiety and depression (r = 0.618, p = 0.000). It can be concluded that there was a high incidence of moderate TMD, headache and neck pain among the volunteers. As higher the perceived level of stress, higher levels of anxiety and depression, and greater the intensity of pain on palpation in the masticatory and cervical muscles. The cervical muscles had low pain pressure threshold values, being lower in the sternocleidomastoid muscle (SCM) compared to other muscles evaluated.